A‐site Cation Engineering for Highly Efficient MAPbI3 Single‐Crystal X‐ray Detector. (23rd October 2019) - Huang, Yanmin; Qiao, Lu; Jiang, Yuanzhi; He, Tingwei; Long, Run; Yang, Fan; Wang, Lin; Lei, Xiaojuan; Yuan, Mingjian; Chen, Jun
Abstract: Metal halide perovskites have emerged as a new generation of X‐ray detector materials. However, large‐sized MAPbI3 single crystals (SCs) still exhibit lower performance than MAPbBr3 SCs in X‐ray detection. DFT (density functional theory) simulations suggest the problem could be overcome by alloying large‐sized cations at the A site. The alloyed process could notably decrease the electron–phonon coupling strength and increase the material defect formation energy. Accordingly, centimeter‐sized alloyed DMAMAPbI3 (DMA=dimethylammonium) and GAMAPbI3 (GA=guanidinium) SCs are obtained. Electrical characterizations confirm the GAMAPbI3 SCs display improved charge collection efficiency. It also exhibits a remarkable reduction of dark current, an important figure of merit for X‐ray detectors. With a judiciously designed device architecture, the overall detector performance confirms GAMAPbI3 SCs as one of the most sensitive perovskite X‐ray detectors to date. Abstract : Detektivarbeit : DFT‐Simulationen und experimentelle Ergebnisse deuten darauf hin, dass ein legiertes großes Kation in der A‐Stelle die Leistung von einkristallinen MAPbI3 ‐Röntgendetektoren (MA=CH3 NH3 ) verbessern kann. So wurden legierte GAMAPbI3 ‐Einkristalle (GA=Guanidinium) hergestellt, die exzellente Eigenschaften als Perowskit‐Röntgendetektoren zeigten.